A procedural framework for extension of time (EoT) claim settlement in the Malaysian construction industry / Norazian Mohamad Yusuwan - Mohamad Yusuwan, Norazian (Institute of Graduate Studies, UiTM, 2017)
The construction industry is often burdened by various problems associated with contractual claims that affect not only the administration and management of projects but also disrupt the smooth running of construction activities as well as contribute to the occurrence of disputes between the parties involved. Such disputes will affect harmonious relationships among industry players if they are not tackled in the best possible way. Despite the many studies that have been carried out with regard to improving the management of contract claims, yet very little research has been conducted to address the issue in relation to the extension of time (EoT) claim, specifically as to what constitutes a good EoT claim and the possible measures that can be taken by industry players towards the successful settlement of an EoT claim. Therefore, this study was undertaken with the aim of developing an appropriate framework that can help the parties involved in the construction industry to come up with EoT claims that can be resolved harmoniously without any unnecessary disputes. Prior to the development of such a framework, the practices of industry players in dealing with EoT claims were investigated, contentious issues in relation to EoT claims and the reasons for the rejection of such claims were revealed, and the success elements for EoT claims and initiatives to reduce the likelihood of failure of such claims were identified. The triangulation method comprised of a questionnaire survey, semi-structured interviews and a modified Delphi approach, was employed to achieve the research objectives…